Why and When Team Reflexivity Contributes to Team Performance: A Moderated Mediation Model - Yang, Mengxi; Schloemer, Hilary; Zhu, Zheng; Lin, Yuying; Chen, Wansi; Dong, Niannian (Frontiers in Psychology, 2020)
Team reflexivity has gained popularity as a phenomenon of interest in team research, but mixed theorizing around the relationship between team reflexivity and team performance indicates that the relationship is not fully understood. In an effort to improve our understanding and explain why and when team reflexivity will be conducive to team performance, we examine the role of team diversity as a possible boundary condition and of team decision quality as an explanatory mechanism. Using survey data from 82 teams with 82 leaders and 194 team members, we find that team decision quality is a partial mediator of the relationship between team reflexivity and team performance and that team diversity strengthens this mediating relationship. We also find that team diversity moderates the relationship between team reflexivity and decision quality. Taken together, these findings suggest that reflexivity is most effective in conditions of informational richness, such as when teams have high diversity, as the reflective process allows team members to capitalize on their varied perspectives to improve the quality of their decisions and, thus, their performance.